Low threshold amplified spontaneous emission and ambipolar charge transport in non-volatile liquid fluorene derivatives. Issue 15 (6th January 2016) - Ribierre, Jean-Charles; Zhao, Li; Inoue, Munetomo; Schwartz, Pierre-Olivier; Kim, Ju-Hyung; Yoshida, Kou; Sandanayaka, Atula S. D.; Nakanotani, Hajime; Mager, Loic; Méry, Stéphane; Adachi, Chihaya
Abstract : Ambipolar charge transport and low threshold amplified spontaneous emission are observed in novel highly fluorescent liquid fluorene derivatives. Abstract : Highly fluorescent non-volatile fluidic fluorene derivatives functionalized with siloxane chains were synthesized and used in monolithic solvent-free liquid organic semiconductor distributed feedback lasers. The photoluminescence quantum yield values, the amplified spontaneous emission thresholds and the ambipolar charge carrier mobilities demonstrate that this class of materials is extremely promising for organic fluidic light-emitting and lasing devices.